CRITICAL STUDY ON THE DA’WAH MOVEMENT OF THE MUSLIMAH OF HIZB UT-TAHRIR INDONESIA IN ESTABLISHING AN ISLAMIC SOCIETY IN INDONESIA - Suhartini Suhartini; Achmad Satori Ismail (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This research is a scientific paper arising from a thought of the big amount of women population along with their roles in building society and human civilization. However, empowerment of women, as the subject of da’wah, is still less, both in terms of the quality and the quantity. Hence, women as the da’wah object have not been properly managed. For that reason, the reseachers are interested in studying the activities of the da’wah movement of the Muslimah of Hizb ut-Tahrir Indonesia. The da’wah movement the Muslimah of Hizb ut-Tahrir Indonesia is chosen as the research object since building an Islamic society is related to their central issue of establishing an Islamic Caliphate. For analyzing such an issue, the researches determine the problem formulation, namely: how does the da’wah movement of the Muslimah of Hizb ut-Tahrir Indonesia realize an Islamic society? The method of the research is qualitative, namely by conducting observation along with interviews, library researches, and an analytic description method. The discussion result was obtained through a study of the da’wah movement of the Muslimah of Hizb ut-Tahrir Indonesia by utilizing da’wah approaches, both in terms of the manhaj, da’wah elements, and da’wah objectives, and then analyzing them. The result discloses that the da’wah movement of the Muslimah of Hizb ut-Tahrir Indonesia focuses on the da’wah of thoughts only. Therefore, those who have a vision of realizing an Islamic Caliphate and leading Indonesia will not be able to realize an Islamic society, or even to lead the country or to realize an Islamic Caliphate.